Avaliação da acurácia em detectar a desadaptação entre implante e prótese por meio de tomografia computadorizada de feixe cônico - Carneiro, Vinícius Cavalcanti (2018)
Introduction: the long-term success of osseointegration and implant-supported prostheses is achieved through the fit between abutment and implant platform, which also figure as a requirement for maintance of bone-implant inferface. In cases where the adaptation is not effective, misfits at the implant-abutment joint (IAJ) might be present. Periapical radiographs are often used as a complementary method for misfit detection; however, there are limited evidences that support the use of imaging methods to evaluate the IAJ. Objective: to evaluate the accuracy of three cone beam computed tomography CBCT systems for misfit detection at the IAJ. Method: 32 implants were placed in the region of molars and premolars of eight dried human mandibular jaws. Polyester strips were placed between the implant platforms and porcelain-fused-to-metal crowns in order to simulate gaps of 200-μm, while no strips were placed in the control group (0 μm). Next, specimens were scanned in both conditions, with and without simulated gap, by using the CBCT systems Picasso Trio, OP300 and Scanora 3D. CBCT images were assessed by four evaluators regarding the presence or absence of misfit at IAJ. The contrast resolution of the images was measured by an independent evaluator with the aid of ImageJ software. Statistical analysis included the calculation of diagnostic values, comparison among values of areas under the ROC curves (Az) and Kappa test. Results: intra- and interreproducibility ranged from fair to almost perfect and were lower for OP300 and Scanora 3D. Picasso Trio showed higher diagnostic values (accuracy = 0.84, sensitivity = 0.83, specificity = 0.85, positive predictive value = 0.85, negative predictive value = 0.84) and Az (0.86; p<.05). Picasso Trio obtained higher contrast resolution than OP300 and Scanora 3D systems. Conclusion: in comparison to OP300 and Scanora 3D systems, images acquired with Picasso Trio allowed a more accurate misfit detection at IAJ.